2018
DOI: 10.1080/09658211.2018.1498107
|View full text |Cite
|
Sign up to set email alerts
|

Mood impedes monitoring of emotional false memories: evidence for the associative theories

Abstract: In the present experiment, we investigated whether warnings provided at the time of retrieval would reduce emotional false memories in the Deese-Roediger-McDermott (DRM) paradigm. The provision of retrieval warnings allowed us to test specific predictions based on the associative theories (e.g., Activation-Monitoring Theory; AMT) and Fuzzy-Trace Theory (FTT) that have been used to account for false memories in the DRM paradigm. Participants were randomly assigned to either a no-warning group or a retrieval-war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Consistent with prior research (Brainerd et al, 2010; Brainerd, Reyna, & Ceci, 2008; Howe et al, 2010; Zhang et al, 2019b), both age groups in the present experiment exhibited a higher rate of false memory for negative lists than for positive or neutral lists. This finding can be accounted for by FTT and AAT.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with prior research (Brainerd et al, 2010; Brainerd, Reyna, & Ceci, 2008; Howe et al, 2010; Zhang et al, 2019b), both age groups in the present experiment exhibited a higher rate of false memory for negative lists than for positive or neutral lists. This finding can be accounted for by FTT and AAT.…”
Section: Discussionsupporting
confidence: 91%
“…Investigating the combined effects of emotional valence and mood on age-related changes in false memory provides an opportunity to test different predictions based on AAT and FTT. When it comes to mood, Bower’s (1981) network theory is often combined with AAT to explain the mood-congruent false memory effect (e.g., Knott & Thorley, 2014; Ruci et al, 2009; Zhang et al, 2019b). According to the network theory of mood, a given mood (e.g., sadness) is represented as a node in memory that links relevant attributes such as words and concepts (e.g., tears, sorrow, upset, etc.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect warrants close attention, given that researchers typically measure MCM in terms of improved memory accuracy (when tested as such in encoding-retrieval paradigms). Yet, a number of studies have consistently demonstrated the presence of mood-congruent false memory specifically in the Deese-Roediger-McDermott (DRM) paradigm (Deese, 1959;Roediger & McDermott, 1995), whereby participants falsely recognize semantically related, mood-congruent lures when tested on a series of previously encoded word lists (Bland et al, 2016;Knott & Thorley, 2014;Ruci et al, 2009;Zhang et al, 2017Zhang et al, , 2019. In these experiments, mood induction occurs prior to encoding, followed by listening to or reading several lists of closely related words (e.g., horror, scream, monster, panic, fright).…”
Section: Mood-congruent False Memorymentioning
confidence: 99%
“…Crucially, this mistiming of SW- spindles was not related to overnight memory procedural consolidation. Indeed, previous studies manipulating SW-spindles either through medication or transcranial stimulation, have shown only benefits for verbal and declarative memory consolidation [61, 62] but not procedural memory consolidation [63]. Thus, such changes might relate more to structural changes in hippocampal-cortical networks [26,59,6466] related to degradation in patients than as a direct proxy for memory consolidation.…”
Section: Discussionmentioning
confidence: 99%